Why Not Transplant Nephrology? A Survey of US Nephrology Fellows - Abhinaya Sridhar; Kurtis Pivert; Dinushika Mohottige; Kirk N. Campbell; Samira S. Farouk (Kidney Medicine)
Rationale & Objective: The current transplant nephrology workforce may be inadequate to care for the growing population of kidney transplant recipients, particularly as the United States aims to increase kidney transplantation rates. Although transplant nephrology fellowship programs experience similar challenges as general nephrology programs in filling positions, few studies have explored nephrology fellows’ perspectives on transplant careers. We aimed to describe nephrology fellows’ interest in transplant nephrology careers, training experiences, and potential factors influencing transplant nephrology career interests. Study Design: A cross-sectional survey-based study was conducted among US nephrology fellows. Setting & Participants: An electronic survey was distributed in 2024 to 962 current adult, pediatric, and adult and pediatric nephrology fellows in training via the American Society of Nephrology. Exposure: Prior transplant experiences. Outcome: Responses to survey items. Analytical Approach: Descriptive statistics and a χ2 test for independence evaluating relationship between respondents’ transplant rotation experiences and their likelihood of pursuing transplant nephrology. Results: The survey response rate was 45%. 23% (90/393) were somewhat/highly likely to pursue transplant nephrology fellowship. Those less likely to pursue transplant nephrology cited additional training time (66%), inadequate compensation (37%), lifestyle/work-life balance (34%), job availability (23%), and focus on immunology (23%). Free-text responses mentioned challenges with the surgical team as a deterrent. Transplant experiences were similar between those who were likely and those who were not likely to pursue transplant. Of those likely to pursue transplant (n = 90), 19% (17/90) indicated that the introduction of a hypothetical transplant nephrology certification examination would make them not likely to pursue a transplant nephrology career. Limitations: Nonresponse bias. Conclusions: This first survey to assess nephrology fellows’ interest in transplant nephrology careers identified several potential barriers to the lack of interest in transplant nephrology that may serve as areas for intervention in the future.